Hubungan Pendidikan Keluarga dengan Perilaku Moral Remaja di Nagari Kurnia Koto Salak Kecamatan Sungai Rumbai Kabupaten Dharmasraya - Isnaini z, Nadia; Irmawita, Irmawita (Universitas Negeri Padang, 2023)
The low moral conduct of teenagers in Nagari Koto Salak, Sungai Rumbai District, Dharmasraya Regency inspired this study. It is thought that the low moral behavior of these teenagers is influenced by parental education. The study's objectives were as follows: (1) to find out the description of family education in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency; (2) knowing the description of the moral behavior of adolescents in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency; (3) knowing the relationship between family education and adolescent moral behavior in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency. The correlational quantitative approach was utilized in this study with a population of 48 persons, and the sample included 65% of the entire population, namely 30 people. Data gathering methods employing questionnaires are combined with data analysis methods employing percentages and product moments. The results showed that (1) family education in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency was classified as low; (2) the moral behavior of adolescents in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency was categorized as low; (3) there is a positive and significant relationship between family education and adolescent moral behavior in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency.